A Study on Etiology, Clinical Features and Complications of Chronic Kidney Disease Patients - Muhammad Ubaid, Ahsan Mobin, Imtiaz Manzoor, Muhammad Rehan, Zahid Qadri, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Chronic kidney disease (CKD) is a major health issue that encompasses a variety of pathophysiological processes mostly related to declining rate of glomerular filtration and abnormal kidney function. Globally, the incidence of chronic kidney disease is increasing due to hypertension, diabetes, and cardiovascular disease. The present study aimed to investigate the etiology, clinical features, and complications of chronic kidney disease patients. Methodology: This cross-sectional study was conducted on 136 chronic kidney disease patients admitted to the Department of Medicine of Mamji Hospital, Karachi Pakistan from January 2021 to December 2021. Prior to study conduction, ethical approval from the research and ethical committee of the institute was taken. Informed consent was obtained from each individual. Demographic details, para-clinical and clinical features, etiology, and therapeutic features were the different outcome variables. Clinical examinations with detailed history and laboratory investigations were assessed. For laboratory examinations, urine and blood samples from each participant were taken. Data analysis with detailed descriptive statistics was carried out in SPSS version 25. Results: Out of 136 CKD patients, there were 74 (54.4%) male and 62 (45.6%) females. The overall mean age was 38.6±4.8 years. Age-wise distribution of the participants was as: 23 (16.9%) 15-25 years, 38 (27.9%) 26-35 years, 34 (25%) 36-45 years, 26 (19.1%) 46-55 years, and 15 (11.1%) >55 years. The chronic kidney disease associated comorbidities were high blood pressure (HBP) 64 (47.1%), human immunodeficiency virus (HIV) 25 (18.4%), Diabetic sugar 21 (15.4%), heart disease 19 (14%), and sickle cell anemia 7 (5.1%). Lesion diagnosis was found in 61 (44.9%) patients. The most prevalent diagnosis was chronic glomerulonephritis (CGN), Glam nephropathy, and vascular nephropathies presented in 27 (19.9%), 18 (13.2%), and 16 (11.8%) respectively. Intermediate 69 (50.7%), Hypertensive nephropathy 20 (14.7%), HIV-related nephropathy 17 (12.5%), Diabetic nephropathy 15 (11%), Primary segmental and focal hyalinosis 11 (8.2%), and Autosomal dominant polycystic kidney disease 4 (2.9%) were the different etiology diagnosed in CKD patients. The chronic disease complications such as Anemia, hyperkalaemia, hyperuricemia, uremic encephalopathy, right femoral venous thrombosis, and acute pulmonary edema were seen in 107 (78.7%), 54 (39.7%), 13 (9.6%), 9 (6.6%), 2 (1.5%), and 8 (5.9%) respectively. Conclusion: The present study concluded that hypertension, cardiovascular disease, diabetes, and HIV are the different predominant risk factors for chronic kidney disease. Also, the most prevalent etiology of the CKD was chronic glomerulonephritis (CGN) followed by Diabetic nephropathy in CKD patients. Anemia was the prevalent complication followed by hyperkalemia and hyperuricemia. Swelling at lower limb and weakness were the common symptoms of chronic kidney disease. Keywords: Etiology, Clinical features, Complications, Chronic Kidney Disease.